STRATEGI KEPEMIMPINAN KYAI DALAM MENUMBUHKAN JIWA KEWIRAUSAHAAN SANTRI DI ERA DIGITAL (Studi Kasus Di Pondok Pesantren Bahrul Maghfiroh Kota Malang) - Sari, Erma Yunita; Nasith, Ali; Aziz, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The digital era has brought fundamental changes to Islamic boarding schools (pesantren), which are expected to produce santri who are independent, innovative, and competitive without abandoning Islamic values. This study aims to: (1) analyze the kyai's leadership vision in fostering the entrepreneurial spirit of santri in the digital era, (2) describe the leadership approaches applied by the kyai, and (3) examine the impact of kyai leadership at Bahrul Maghfiroh Islamic Boarding School, Malang City. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation, analyzed using the interactive model of Miles, Huberman, and Saldana. The findings indicate: (1) The kyai's leadership vision is oriented toward the holistic development of santri independence encompassing spiritual, character, and economic dimensions, with digital technology as an entrepreneurship support tool aligned with Islamic ethics; (2) The leadership approach is implemented through three integrated strategies: exemplary leadership, santri development and empowerment through the Santri Preneur program and Vocational Training Center (BLK) using learning by doing, and digitalization through an AI laboratory and social media-based digital marketing; (3) The impact is manifested in cognitive, affective, and psychomotor dimensions, evidenced by increased revenue of the koi fish business unit reaching IDR 60 million via TikTok, achieving first place in a national inter-pesantren entrepreneurship competition, and santri initiating digital-based independent businesses.